2015
DOI: 10.1007/s11746-015-2771-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Specialty Natural Micronutrients in Certain Oilseeds and Oils: Plastochromanol‐8, Resveratrol, 5‐Hydroxytryptamine Phenylpropanoid Amides, Lanosterol, Ergosterol and Cyclolinopeptides

Abstract: The current concern for health has raised the importance of natural micronutrients in edible oils and fats. Different from common micronutrients, e.g., tocopherols, tocotrienols, stigmasterol and sitosterol, new and emerging specialty micronutrients, such as plastochromanol‐8, resveratrol, phenylpropanoid amides of 5‐hydroxytryptamine, lanosterol, ergosterol and cyclolinopeptides, are becoming increasingly popular among health‐conscious people. The first three are phenolic compounds, the forth and fifth sterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 89 publications
(150 reference statements)
0
2
0
1
Order By: Relevance
“…It is worth noting that β-sitosterol was not detectable in refined camellia oil. The adsorption of sterols during bleaching and the removal of sterols during the vacuum distillation step of deodorization are considered the main reasons for the losses of β-sitosterol during the refining process [ 42 ]. The results suggested that fresh-pressed and cold-pressed technologies are more favorable for the retention of β-sitosterol.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that β-sitosterol was not detectable in refined camellia oil. The adsorption of sterols during bleaching and the removal of sterols during the vacuum distillation step of deodorization are considered the main reasons for the losses of β-sitosterol during the refining process [ 42 ]. The results suggested that fresh-pressed and cold-pressed technologies are more favorable for the retention of β-sitosterol.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, samples were saponified, hexane-extracted, and, after solvent reduction, directly measured by LC-Orbitrap-HRMS. Due to the high PC-8 content in flaxseed oil (≈250 mg kg −1 oil [11] ) and rapeseed oil (up to ≈90 mg kg −1 oil [11] ), these two matrices were primarily selected by us along with other oils pressed from botanically related species. In addition, a review article of Kruk et al [12] reported the presence of considerable amounts of PC-8 in the leaves of Cecropia sp.…”
Section: Introductionmentioning
confidence: 99%
“…übertrifft die von α-Tocopherol um etwa das 1,5-fache [2]. PC-8 kommt hauptsächlich in Blättern und Samen von Vertretern der Pflanzenfamilien Linaceae und Brassicaceae vor, wobei die entsprechenden Pflanzenöle vergleichsweise hohe Mengen an PC-8 aufweisen (~250 mg PC-8/kg Leinöl) [3].…”
unclassified